Impact of Decision-Making Participation, Work Environment Assessment and Achievement Motivation on Job Satisfaction of Sabang Freeport Concession Board (BPKS) Employees - Nasir; Fahmi, Ijal (Indonesian Journal Economic Review (IJER), 2023)
The purpose of this study is to determine the impact of achievement motivation on participation in the decision-making process, assessment of work environment, and job satisfaction of Free Trade Area Concession Service and Sabang Freeport employees. Respondents were 56 facility employees selected through a rapid sampling sample. Data collection was performed using questionnaires and data were analyzed using multiple statistical linear regression tools. The study found that decision-making involvement, work environment ratings, and achievement motivations had a positive impact on job satisfaction among Sabang Free Trade Zone and Freeport Concession Authority employees. Motivation to achieve has the greatest impact on employee job satisfaction, followed by evaluation of the work environment. Statistical test results show that the values ​​of F count > F table and T count > T table can be simultaneously and partially interpreted as participation in decision-making and evaluation of the working environment of Sabang Free Trade Zone employees. I'm here. and the Freeport Concession Office. Therefore, hypothesis Ha is accepted and hypothesis Ho is rejected. The conclusion drawn from this survey is the job satisfaction of Sabang Free Trade Agreement Agency employees. heavily influenced by employee involvement in the decision-making process, evaluation of the work environment, and employee motivation to perform